A new method for converting extended version of petri nets to fuzzy extended markup language - Solmaz Soltani; Ali Harounabadi (Management Science Letters, 2014)
A model is a simple and straightforward performance of structure and behavior of the system under study expressed as mathematical relations. In fact, with a model, knowledge and information on modeled phenomenon are prepared and the cost and risk of applying actual phenomenon are eliminated. Petri nets, on the other hand, are used to determine the important information on structure and behavior in modeled system and formal models are mainly state dependent requirements. These requirements are significantly indefinite and can be expressed by language variables. If XML labels can express the formal models (Fuzzy Petri net) as the most valid data format, then we will have relationships with other data format. In this study, characteristics of a Fuzzy Colored Petri Net are expressed by fuzzy developed Markup Language labels. Therefore, in addition to fuzzy XML labels, the concept “color” will be used for them. Application and advantages of suggested method will be determined by a case study in bank facility system. The results of the evaluation indicate the advantages of the suggested grammar for supporting elements available in fuzzy formal models.